2
$\begingroup$

Doing research in probability modelling I obtained a decomposition of inverse factorial:

$$\frac{1}{n!}=\sum\limits^n_{i=1}\frac{(-1)^{n+i}}{(i-1)!(n+1-i)!}$$

How can it be proven directly? In what literature can I find it?

P.S. For odd $n$ the equality is trivial because all terms except $\frac{1}{n!}$ vanish. The trick is to prove it for even $n$.

$\endgroup$
2
$\begingroup$

Hint: Note that the formula is equivalent to $$1=\sum\limits_{i=1}^{n}(-1)^{n+i}\cdot \frac{n!}{(i-1)!(n+1-i)!},$$ i.e. $$1=(-1)^n\sum\limits_{i=1}^{n}(-1)^{i}\binom{n}{i-1}.$$

To show this, try using the fact that $\sum\limits_{k=0}^{n}(-1)^k \binom{n}{k}=0$ (which you can show using the binomial theorem).

$\endgroup$
  • 1
    $\begingroup$ Thanks! My vote for your answer is not displayed :( $\endgroup$ – Andrey Rogatkin May 11 at 13:43

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.